Promoting systems thinking and pro-environmental policy support through serious games - Sajjadi, Pejman; Bagher, Mahda M.; Myrick, Jessica G.; Guerriero, Joseph G.; White, Timothy S.; Klippel, Alexander; Swim, Janet K. (Frontiers in Environmental Science, 2022)
We evaluated whether teaching the public about the “critical zone”–the Earth’s outer skin, critical to all life—via a digital serious game can affect adults’ systems thinking about the environment and support policies to protect the environment. An experiment (N = 152) compared the effects of playing “CZ Investigator” versus viewing a static website on systems thinking about the Food-Energy-Water (FEW) nexus and support for relevant public policies. The serious game had the strongest effects on our outcomes of interest for those participants with less past science education. For these individuals, the serious game, relative to the static website, increased perceptions of the strength of interconnections across food, energy, and water systems (p < .01) and support for policies that regulated human impacts on the environment (p < .01). Mediation analysis revealed that increases in systems thinking explain increases in policy support. This group of users also indicated that the game was easier, more enjoyable, and more effective for learning than the website. Mediation analyses also revealed that perceived learning effectiveness was a stronger mediator than ease and enjoyment effects of the game on systems thinking and policy support. These results are valuable for environmental education because understanding interconnections within complex systems is vital for solving environmental problems, particularly for learners with less background in science.